Preparation and physicochemical characterization of prazosin conjugated PLGA nanoparticles for drug delivery of flutamide - Fattahi, Ali (2018)
In the current work, a sustained drug delivery system of flutamide (FLT) was developed using Poly(D,L‑lactide-co-glycolide) (PLGA) decorated bypoly(ethylene glycol) (PEG) grafted prazosin (PLGA-PEG-Praz) as a targeting moiety. In a multi-step reaction, PLGA was linked to PEG and prazosin. The structure of the synthesized polymers was confirmed by FTIR and 1 H-NMR. Flutamide-loaded nanoparticles were prepared by quasi-emulsion solvent diffusion technique. The nanoparticles were evaluated for size, zeta potential, polydispersity index, drug crystallinity, loading efficiency, and release properties. Also, the physicochemical properties of the nanoparticles were analyzed using Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry, and Powder X-Ray Diffractometry (XRD). The particle size of nanoparticles was ranged between 191 and 249 nm. Loading efficiency of nanoparticles was about 43%-69%. Results showed a steady release rate for nanoparticles compared to that of a pure drug powder. SEM characterization confirmed that particles were in nanosize range. DSC and XRPD results verified a decrease in drug crystallinity in the prepared formulations. In conclusion, the results of this study showed that PLGA-PEG-Praz nanoparticles could be a good choice to improve the physicochemical properties of the drug and these formulations can increase Flutamide efficacy